2016
DOI: 10.1017/s003060531600065x
|View full text |Cite
|
Sign up to set email alerts
|

Favourableness and connectivity of a Western Iberian landscape for the reintroduction of the iconic Iberian ibexCapra pyrenaica

Abstract: Traditional land use practices declined throughout many of Europe's rural landscapes during the 20th century. Rewilding (i.e. restoring ecosystem functioning with minimal human intervention) is being pursued in many areas, and restocking or reintroduction of key species is often part of the rewilding strategy. Such programmes require ecological information about the target areas but this is not always available. Using the example of the Iberian ibex Capra pyrenaica within the Rewilding Europe framework we addr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Using a prioritization scheme, we identified potential reintroduction sites that could increase the area occupied by the St Croix ground lizard by 180%. In previous studies, a predictive approach using demographic data demonstrated that sufficiently low levels of threats could allow reintroductions of the Iberian ibex in western Iberia, and the North Island robin and North Island saddleback Philesturnus rufusater in New Zealand (Armstrong & Davidson, 2006; Parlato & Armstrong, 2012; Torres et al, 2016). Our approach differs in that we evaluated suitability across emergent contemporary landscapes, to determine areas best suited for reintroduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a prioritization scheme, we identified potential reintroduction sites that could increase the area occupied by the St Croix ground lizard by 180%. In previous studies, a predictive approach using demographic data demonstrated that sufficiently low levels of threats could allow reintroductions of the Iberian ibex in western Iberia, and the North Island robin and North Island saddleback Philesturnus rufusater in New Zealand (Armstrong & Davidson, 2006; Parlato & Armstrong, 2012; Torres et al, 2016). Our approach differs in that we evaluated suitability across emergent contemporary landscapes, to determine areas best suited for reintroduction.…”
Section: Discussionmentioning
confidence: 99%
“…Successional forests are allowing previously overexploited animals that suffered habitat loss, such as the Puerto Rican parrot Amazona vittata and white-crowned pigeon Patagioenas leucocephala , to recover in Puerto Rico and throughout the Caribbean (Earnhardt et al, 2014; Rivera-Milán et al, 2016). Networks of suitable habitat have been modelled for the Iberian ibex Capra pyrenaica in western Iberia (Torres et al, 2016) and for the North Island robin Petroica longipes in New Zealand (Armstrong & Davidson, 2006). These cases highlight how landscape change over time can support species reintroduction and recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Rebelo and Jones 2010), to determine the environmental potential for invasive/introduced species (e.g. Jimenez-Valverde et al 2011;Torres et al 2016), or to assess the niche similarities between related taxa (e.g. Acevedo et al 2014a), among others.…”
Section: The Transferability Of Sdmsmentioning
confidence: 99%
“…Endangered species reintroductions and translocations are important and increasingly applied conservation interventions to save species from extinction and facilitate their recovery [1, 2]; but, failure rates can be high when not properly planned [24]. For most species, a key determinant of success is identification of the reintroduction landscape, which considers ecological, social, and institutional dimensions [5, 6]. This can be particularly important for species that have large home ranges and those that have the potential to cause human-wildlife conflict.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly critical for wide-ranging species where simply identifying breeding areas or local conditions in the immediate vicinity of the reintroduction site is insufficient. When paired with habitat linkage or population dynamics models, predicting movement probabilities away from reintroduction sites can also provide information necessary for identifying habitats in need of protection [68], comparing likely costs and outcomes of various reintroduction scenarios [9], and for helping to define and quantify recovery targets [10].…”
Section: Introductionmentioning
confidence: 99%